Answer: [B]: " (-6, 9) " .
_______________________________
Explanation:
_______________________________________
Given the following system of equations:
_______________________________________
x + y = 3 ;
y = 9 ;
_________________________________
Substitute "9" for "y" in the first equation; to solve for "x"; we already have our value for "y" ; "y = 9 " ; (given) ;
____________________________
x + 9 = 3 ;
Subtract "9" from EACH side of the equation;
_____________________________________
x + 9 − 9 = 3 − 9 ;
to get:
_____________________________________
x = -6 .
_____________________________________
Check our answer:
x + y = 3
________________
-6 + 9 =? 3 ? Yes!
_____________________
The answer for the system of equations is:
_____________________________________
x = -6, y = 9 ; or, write as: (-6, 9) .
_____________________________________
which is: Answer choice: [B]: " (-6, 9) " .
_____________________________________